Coaching como ferramenta de gestão de pessoas: - Costa, Daniella Coêlho (Universidade Federal do Tocantins, 2023)
This article aims to analyze through an exploratory study, with Coach William Licursi, resident in Brasilia, in order to obtain information about its operations in the coaching process. Also introduces concepts related to the coaching activity, shows how the leadership and coaching are related and emphasizes the importance of organizations have a follow up with a professional like the coach. With respect to research, this was accomplished through an interview with a professional, looking for, in the view of the Coach, describe the processes of coaching; What's your target audience; What are the steps of their advice; the tools and methods used for the execution of the work and the results obtained at the end of the consultancy, and for this, we used bibliographical research. Overall, the research concludes that the use of the coaching process can be an important tool used by the Personnel Management in companies.